Structure of porous silicon films - Zhanabaev, Z.Zh.; Timoshenko, V.Yu.; Turmukhambetov, A.Zh.; Grevtseva, T.Yu.; Assilbayeva, R.B. (Ye.A.Buketov Karaganda State University Publishing house, 2017)
The present work is devoted to experimental and theoretical study of silicon films grown by metal-induced chemical etching. Photos of film surfaces were obtained by use of scanning electron microscope. It was shown that variation of etching time leads to changing of informational entropy of the films. This parameter increases for lateral sides of surfaces, and decreases for their top layers. This fact can be used for explanation of ambiguous effects at reflection of photons from surfaces of porous silicon films.
Keywords: porous silicon; nanostructure; morphology; metal-induced chemical etching; informational entropy